On the Philosophers’ Exile and Pere Coromines’ Desterro - Sales-Coderch, Jordi (Journal of Catalan Intellectual History, 2011)
This article suggests a reconsideration of the term “exile” as it is referred to the Catalan thinkers since the armed conflict of 1936-1939. “Inner exile” is a label whose use frequently obeys to ideological and personal considerations rather than to an objective characterisation. Thus, what serves to discredit some authors is neglected for others who enjoy a positive characterisation . This is also the case of “exile”. Pere Coromines [1870-1939] stands here as an initial example. key words exile, inner exile, Pere Coromines.